IS6110 Copy Number in Multi-Host Mycobacterium bovis Strains Circulating in Bovine Tuberculosis Endemic French Regions - Charles, Ciriac; Conde, Cyril; Biet, Franck; Boschiroli, Maria Laura; Michelet, Lorraine (Frontiers in Microbiology, 2022)
IS6110 is an insertion sequence found in the Mycobacterium tuberculosis complex –to which M. bovis belongs-, which can play a role in genome plasticity and in bacterium evolution. In this article, the abundance and location of IS6110 on M. bovis genomic data of French animal field strains was studied. A first analysis was performed on a panel of 81 strains that reflect the national M. bovis population's genetic diversity. The results show that more than a third of them are IS6110 multi-copy and that 10% have IS6110 in a high copy number (more than 6 copies). Multi-copy strains are those circulating in the regions where prevalence was above the national average. Further study of 93 such strains, with an IS6110 copy number of 10-12, showed stability of IS6110 copy number and genome location over time and between host species.. The correlation between M. bovis multi-copy strains and high bTB prevalence leads us to consider whether their epidemiological success could be partly due to genetic changes originated by IS6110 transposition.